2017
DOI: 10.1111/jnu.12301
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Work Life, Nurses’ Intention to Leave the Profession, and Nurses Leaving the Profession: A One‐Year Prospective Survey

Abstract: This study illustrates that nurse managers could provide effective interventions to ameliorate the milieu of respect and autonomy aspect of quality of work life to prevent nurses from leaving their profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 24 publications
4
64
1
5
Order By: Relevance
“…Lee et al found that as many as 720 nurses (56.1%) had a turnover intention through a survey of 1283 hospital nurses in Taiwan [12]. The score of work stressor of ICU nurses was higher than that of other department nurses [4], and the turnover intention of ICU nurses was higher than that of general outpatient nurses [13].…”
Section: The Importance Of Investigating the Quality Of Work Life Of mentioning
confidence: 99%
“…Lee et al found that as many as 720 nurses (56.1%) had a turnover intention through a survey of 1283 hospital nurses in Taiwan [12]. The score of work stressor of ICU nurses was higher than that of other department nurses [4], and the turnover intention of ICU nurses was higher than that of general outpatient nurses [13].…”
Section: The Importance Of Investigating the Quality Of Work Life Of mentioning
confidence: 99%
“…Professional turnover would occur when nurses have a strong intention to leave the profession (Lee et al, ), indicating the importance of reducing professional turnover intention. Actual professional turnover can be reduced by professional commitment (Chang et al, ) but research is needed to examine how the three aspects of professional commitment may help reduce professional turnover intention.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The relevant literature has examined sources of nurses’ professional turnover intentions, including psychosomatic complaints (Jourdain & Chênevert, ), the low level of nurse participation in hospital affairs, practice environment (Numminen, Leino‐Kilpi, Isoaho, & Meretoja, ), respect, autonomy, quality of work life (Lee et al, ), and aspects of professional commitment (Chang et al, ; Guerrero, Chênevert, & Kilroy, ). These studies verified the importance of workplace and career issues in determining nurses’ professional turnover.…”
Section: Introductionmentioning
confidence: 99%
“…The nursing literature has explored the antecedents of nurses' intentions to leave an organisation and/or the profession, including a deteriorating work environment (Al-Hamdan, Manojlovich, & Tanima, 2017), workplace violence (Zhao et al, 2018), psychological capital (Brunetto, Rodwell, Shacklock, Farr-Wharton, & Demir, 2016), quality of work life (Lee et al, 2017), job satisfaction (Tsai & Wu, 2010), organisational commitment (Cheng & Liou, 2011), affective commitment (Perreira, Berta, & Herbert, 2018), continuance commitment (Chang et al, 2015) and normative commitment (Gambino, 2010). Among the aspects of deteriorated work environment, a lack of managerial support (Brunetto et al, 2016;Gillet et al, 2018) and social support from peers (Bruyneel, Thoelen, Adriaenssens, & Sermeus, 2017;Rodwell, McWilliams, & Gulyas, 2017) motivated nurses to leave the profession.…”
Section: Introductionmentioning
confidence: 99%